Investment banking : theory and practice. - Gardener, Edward P. M.; Molyneux, Philip (London : Euromoney, 1995)
This guide draws upon the knowledge of academics and practitioners in this field. This books provides discussion on, amongst other subjects, the EC and the supervision of investment banking, the international money markets and the future of investment banking.
Includes bibliographical references
oif 18/07/14
Loan
Keywords: Investment banking